Manejo do ácaro rajado Tetranychus urticae Koch, em morangueiro, com ênfase em controle biológico e produtos alternativos - Ferreira, Nilson Zacarias Bernabé (2016)
The strawberry crop has become increasingly important due its organoleptic and nutraceutical characteristics, and has been mainly cultivated by small family farmers. Although the strawberry fruit is much appreciated by consumers, it is often regarded as a product that presents health risks due to possible pesticide residues. Among the main pests that occur in the strawberry crop, the spider mite, Tetranychus urticae Koch, is without a doubt the most important, causing decreased production, affecting the quality of the product and contributing to an increase in the use of pesticides. This study aimed to assess the viability of mass rearing of predatory mites of spider mite belonging to the Phytoseiidae family for farmers; the effectiveness of control of these mites associated with the implementation of alternative products used in agroecology; and the effectiveness of these products on the mite and its selectivity to predatory mites. The following products were evaluated: Azamax (3 mL/L), association Azamax (3 mL/L) with neutral detergent (10 mL/L), neutral detergent (10 mL/L), Beauveria bassiana (10 g/L), Kumulus (2.5 g/L), and association of homeopathic products Staphysagria 30 CH (0.5 mL/L) and Sulphur 30 CH (0.5 mL/L). It was found in the field experiment a great control efficiency of predatory mites used in combination with different alternatives or isolated. In the experiments conducted in the laboratory, with products using Potter spray tower, it was observed that the treatments with Azamax, detergent and Azamax + detergent were the most efficient in controlling spider mite, T. urticae, whereas Azamax and Azamax + detergent were selective for predatory mites.